Epidermis and Enamel: Insights Into Gnawing Criticisms of Human Bitemark Evidence. (June 2018) - Barsley, Robert E.; Bernstein, Mark L.; Brumit, Paula C.; Dorion, Robert B.J.; Golden, Gregory S.; Lewis, James M.; McDowell, John D.; Metcalf, Roger D.; Senn, David R.; Sweet, David; Weems, Richard A.
Abstract : Abstract: Critics describe forensic dentists' management of bitemark evidence as junk science with poor sensitivity and specificity and state that linkages to a biter are unfounded. Those vocal critics, supported by certain media, characterize odontologists' previous errors as egregious and petition government agencies to render bitemark evidence inadmissible. Odontologists acknowledge that some practitioners have made past mistakes. However, it does not logically follow that the errors of a few identify a systemic failure of bitemark analysis. Scrutiny of the contentious cases shows that most occurred 20 to 40 years ago. Since then, research has been ongoing and more conservative guidelines, standards, and terminology have been adopted so that past errors are no longer reflective of current safeguards. The authors recommend a comprehensive root analysis of problem cases to be used to determine all the factors that contributed to those previous problems. The legal community also shares responsibility for some of the past erroneous convictions. Currently, most proffered bitemark cases referred to odontologists do not reach courts because those forensic dentists dismiss them as unacceptable or insufficient for analysis. Most bitemark evidence cases have been properly managed by odontologists. Bitemark evidence and testimony remain relevant and have made significant contributions in the justice system.